Svampar associerade med raps - Dahlberg, Caroline (2009)
Oilseed rape is an important crop in Sweden and is grown on about 90000 ha today. The interest in oil seed pro-duction is increasing because of growing demand and high prices for oil seed both in Sweden and Europe. However, an increased intensity in the oil seed production can bring higher risk of yield losses due to fungal diseases. The purpose of this study was to investigate what different fungi are associated with oilseed rape under field conditions and if their incidence is correlated to crop establishment problems. This study was carried out in three parts: 1) investigations on fungal community structure in roots and rhizosphere soils from young spring- and winter rape plants sampled in failed respectively good establishment patches in four fields, 2) investigations on the pathogenicity of fungi isolated from oilseed rape in controlled environment and 3) investigations on the effect of different fungicide seed treatments on germination and early plant development in a field soil naturally infested with damping off- and Verticillium wilt pathogens.